Middle Eastern Geopolitics and the Transformation of Islamic Law: An Analysis of Islamic Politics in Muslim Countries - Kunkunrat; Ade Priangani; Willya Achmad (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
This study examines the significant influence of regional geopolitical dynamics on the evolution of Islamic law, emphasizing the consequences of legal policies and reforms in the Middle East for non-Arab Muslim countries, particularly Indonesia and Malaysia. Using a qualitative research design and a comparative case study approach, the research is grounded in a constructivist-interpretivist framework and draws on in-depth interviews with scholars, policymakers, journalists, and observers of Islamic politics. Public discourse, policy, and legal documents are also thoroughly analyzed. The study reveals that the evolution of Islamic law is shaped by both international geopolitical tensions and domestic political factors, with distinct manifestations, including conservative theocratic, revolutionary, ideological, secular-pragmatic, and modernist approaches. Notably, geopolitical rivalries in the Middle East have exacerbated sectarian divisions in the Islamic legal discourse. While, the application of Islamic law outside the region is increasingly being integrated into constitutional and democratic frameworks. By addressing the intersection of Islamic law, politics, and geopolitics, this research advocates for promoting moderate Islamic constitutionalism, fostering transnational legal pluralism, and advocating for a more distinct separation between religious and political interests. The study contributes novel perspectives on how Islamic law adapts and evolves in response to contemporary global political shifts, offering critical insights for policymakers and scholars engaged with legal and political transformation in the Muslim world.